Integrating Bloom's Taxonomy into the Design of Final English Tests for Eighth Graders - Ratnasari, Luky Dwi; Syafi'ul Anam; Ali Mustofa (Universitas Islam Lamongan, 2025)
Testing is essential in education because it helps teachers measure how much students have learned. Teachers typically use multiple-choice and essay questions for this purpose. This research examined what types of thinking skills English teachers focus on when creating final exams for eighth-grade students, using Bloom's educational framework as a guide. The study also looked at the difficulties teachers encounter while developing these tests. The researchers used interviews and systematic observation methods to gather information. They analyzed a 50-question test that included 45 multiple-choice items and 5 essay questions. The results revealed that the test mainly assessed three types of thinking: memorizing information, comprehending concepts, and analyzing material, with comprehension questions being the most common. Teachers identified two main challenges: limited time for test development and difficulty categorizing questions according to Bloom’s taxonomy. To address these issues, they suggested scheduling test creation during holidays and offering clearer institutional guidelines. They also recommended enhancing teachers’ understanding of Bloom’s taxonomy to improve test design. This study contributes to English language assessment by revealing a strong focus on lower-order thinking skills. It highlights the need for professional development and institutional support to help teachers design more balanced assessments that include higher-order thinking skills. Such improvements can lead to more effective language assessment practices aligned with broader educational goals.